Translation of Majāz Mursal in Mushaf Sundawi and Lenyepaneun Holy Verse - Hermawan, Acep; Odang, Odang; Abdul Manan, Wahdan; Alsuhili, Belal Abdullah Ahmed Moqbel (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2024)
This research aims to describe the techniques, accuracy, and pedagogical implications of translating Quranic majÄz mursal into Sundanese in the books Ayat Suci Lenyepaneun and Mushaf Sundawi. Using a qualitative approach with content and discourse analysis methods, data were collected through library research techniques. The findings reveal that in the first book, transposition techniques consist of 54% transfer, 26% substitution, and 20% others, while equivalence techniques include 48% correspondence, 50% description, and 2% others. In the second book, transposition techniques comprise 51% transfer, 21% substitution, and 28% others, while equivalence techniques include 41% correspondence, 49% description, and 10% others. Regarding accuracy, the first book achieves 37% very accurate, 12% accurate, 51% less accurate, and 0% inaccurate, while the second book achieves 35% very accurate, 12% accurate, 53% less accurate, and 0% inaccurate. Practical steps for teaching translation are recommended, including analysis, transfer, restructuring, evaluation, and revision. These findings emphasize the importance of systematic strategies to ensure accurate translations of Quranic texts into regional languages, highlighting the need for translators to master linguistic and cultural nuances. Future research should develop standardized guidelines for Quranic translation, explore advanced translation technologies, and foster collaboration among linguists, theologians, and educators to enhance accuracy and accessibility.